NOSQL Database: Opportunities and Applications - Kharade, Jyoti; Kale, Anil Rama (International Journal of Computer Sciences and Engineering, 2025)
In Today’s digital generation the growth of IT industries gradually increase with the volume of data which is generated by the most of applications. To handle such a large amount of data Relational Database are not sufficient. No SQL database is an emerging alternative to the relational database which provides high scalability, performance and high availability. The paper, discuss about different types of NoSQL database with its opportunities and applications.